Integration of a Generalized Ratio of Polynomials - Matthew J. Brandsema; Donovan E. Brocker (Mathematics, 2021)
This paper provides a closed-form solution to the indefinite integral of a ratio of generalized polynomials where the denominator polynomial is raised to the general order <semantics>r∈Z+</semantics>. Such an integral arises in physics and engineering, the solution of which allows for closed-form analysis.